TINJAUAN TENTANG IMPLEMENTASI PROGAM PELESTARIAN KESENIAN DAN KEBUDAYAAN LOKAL DI KABUPATEN KUTAI BARAT - Riski Aprianto Hului (ADMINISTRASI PUBLIK, 2020)
Riski Apriyanto Hului, Overview of the Implementation of the Local Arts and Culture Preservation Program in West Kutai Regency”. Under the guidance of Mr. H. Ahmad Jubaidi S.Sos, M.Si and Mr. Suhardiman, S.Sos, M.SiThe purpose of this study was to find out and describe the implementation of the local arts and culture preservation program in West Kutai Regency, as well as the supporting and inhibiting factors of the conservation.The type of research used by the researcher is a type of qualitative descriptive research. Informants include, Head of Education and Culture Office of West Kutai Regency, Head of Culture, Education and Culture Office of West Kutai Regency. Performers of arts/craft makers (Fipianus Mudi and Nyoman). Traditional figures, culture, art figures and elements of Millennials, Students, Students. Data analysis used in this research is qualitative data analysis method.Based on the results of the analysis and discussion, it is known that the policy for the preservation of local arts and culture in West Kutai Regency has received enough attention and support from the Regent of West Kutai through the Department of Education and Culture, support in the form of fostering art groups, art performers, craftsmen, constructing buildings. customs and arts, assistance in performing arts during construction exhibitions and also the annual program of local arts festivals.Implementation of policies for preserving local arts and culture programs, carrying out large traditional ceremonies such as: death ceremonies in the form of Kwangkey, traditional ceremonies as a form of gratitude, such as Ngugu Tautn. Gantar dance performances, Bawo dances, Ngelewai dances, and dance creations which are a combination of traditional dance and modern dance. Meanwhile, the art of sound can be seen in Rijoq's song, which is sung during Rijoq's music performance.Support from the local government and related agencies in collaboration with the province to provide assistance to art actors such as musical instruments to every art studio and schools and later there will be an artist movement activity to enter school which aims to develop art by training children starting from elementary school, junior high school and high school in order to be able to develop and preserve local arts and culture in the district of West Kutai.